Blood inflammatory and endothelial markers in women with von Willebrand disease. - Igor Govorov; Katarina Bremme; Anders Larsson; Margareta Holmström; Eduard Komlichenko; Roza Chaireti; Miriam Mints (PLoS ONE, 2019)
Introduction VWD-affected females often experience menorrhagia. Periodical fluctuations of the sex steroids during the menstrual cycle cause changes both in the coagulation and immune system. The aim of the current study was to assess the changes in selected inflammatory and endothelial markers in women with VWD during two phases of the menstrual cycle (follicular and luteal) and to compare it with corresponding data from healthy controls. Materials and methods The study group included 12 VWD-affected females with regular menstrual cycle, with none of them being prescribed hormone treatment. They were not pregnant or breastfeeding. The control group consisted of 102 healthy females, matched for age and BMI. Results Within the VWD group, endostatin was higher during the follicular phase, compared to the luteal phase, although the difference was not significant (p = 0.062). sICAM-1 and IL-6 were higher in VWD-affected females, compared to the controls, sVCAM-1, cathepsin S and sP-selectin were lower (p<0.003 for all cases). The pattern was constant throughout the menstrual cycle. Conclusions Higher levels of endostatin during early follicular phase could potentially predispose women with VWD to the development of heavy menstrual bleeding, due to antiangiogenic properties and ability to suppress several coagulation factors. Lower p-selectin levels in VWD group, compared to controls, may also contribute to the bleeding tendency. Changes in other proteins, involved in angiogenesis are hypothetically related to the formation of angiodysplasia-common complication of VWF deficiency. The latter statement requires confirmation in larger studies.